2012
DOI: 10.1016/j.jalz.2012.05.2187
|View full text |Cite
|
Sign up to set email alerts
|

The ADAS‐Cog revisited: Novel composite scales based on ADAS‐Cog to improve efficiency in MCI and early AD trials

Abstract: Background The Alzheimer’s Disease Assessment Scale-Cognitive (ADAS-Cog) has been used widely as a cognitive end point in Alzheimer’s Disease (AD) clinical trials. Efforts to treat AD pathology at earlier stages have also used ADAS-Cog, but failure in these trials can be difficult to interpret because the scale has well-known ceiling effects that limit its use in mild cognitive impairment (MCI) and early AD. A wealth of data exists in ADAS-Cog from both historical trials and contemporary longitudinal natural h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 30 publications
(29 reference statements)
2
69
0
Order By: Relevance
“…Comparing to the composite scores proposed by other researchers using the ADNI data, all of the composites included some items from the memory domain of ADAS-cog, and all items from the memory domain of CDR. Most of the other composites did not use the functional assessment FAQ whereas ours and "TriAD-G" by Raghavan and colleagues [12] used FAQ to improve sensitivity. None of the studies that examined all available clinical scales in ADNI has identified Executive Function measures (e.g., Trail Making, Digit Symbol, Digit Span, Category Fluency tests) in the development of sensitive composites.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Comparing to the composite scores proposed by other researchers using the ADNI data, all of the composites included some items from the memory domain of ADAS-cog, and all items from the memory domain of CDR. Most of the other composites did not use the functional assessment FAQ whereas ours and "TriAD-G" by Raghavan and colleagues [12] used FAQ to improve sensitivity. None of the studies that examined all available clinical scales in ADNI has identified Executive Function measures (e.g., Trail Making, Digit Symbol, Digit Span, Category Fluency tests) in the development of sensitive composites.…”
Section: Discussionmentioning
confidence: 95%
“…The selected items were combined using weighting factors to maximize the sensitivity of the composite. Nandini and colleagues [12] proposed two composite scores on the basis of ADNI-1 clinical data. The first one is "TriAD," a cognitive endpoint combining Word Recall, Delayed Word Recall, Orientation, and CDR cognitive components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Established instruments to measure cognition lack sensitivity and responsiveness in early stages of the AD process (e.g., Raghavan et al [6]). CAMD's most recent project aims to address this problem by advancing a composite clinical outcome assessment tool built from elements of existing scales through a formal regulatory path for qualification as a primary outcome measure for predementia AD trials.…”
Section: Conceptual and Regulatory Backgroundmentioning
confidence: 99%